1980
DOI: 10.1080/00288233.1980.10417859
|View full text |Cite
|
Sign up to set email alerts
|

I. Occurrence and evidence for the use of nitrogen as a control measure

Abstract: The occurrence of blind seed disease of ryegrass in New Zealand has declined over the last 20 years. During 1948-1960, more than 70% of ryegrass seed samples tested were infected by the pathogen, and mean infection levels per seed line, although fluctuating according to the season, averaged 12%. Levels of over 20% were recorded in 1950, 1952, and 1958. Since then, both the percentage of infected samples and the mean infection level per sample have declined, and during [1976][1977][1978], 27% of seed samples te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Most common were F. avenaceum > M. nivale > F. graminearu > F. culmorum > F. poae. This survey is noteworthy for two reasons: firstly, the results are very similar to those reported by Hampton (1980), illustrating the fact that the systemic seed treatments in use for the last 20 years do not effectively control Fusarium spp. (indeed, the incidence of Fusarium spp.…”
Section: The Current Situationsupporting
confidence: 74%
See 3 more Smart Citations
“…Most common were F. avenaceum > M. nivale > F. graminearu > F. culmorum > F. poae. This survey is noteworthy for two reasons: firstly, the results are very similar to those reported by Hampton (1980), illustrating the fact that the systemic seed treatments in use for the last 20 years do not effectively control Fusarium spp. (indeed, the incidence of Fusarium spp.…”
Section: The Current Situationsupporting
confidence: 74%
“…The committee continued to meet until the late 1950s. Control strategies investigated included breeding for disease resistance, fungicide seed treatment, and fertiliser management (see Hampton & Scott 1980), but none were successful as between 1948 and 1960, 70% of ryegrass seed samples were positive for blind seed disease, with an average infection level of 12% (Hampton & Scott 1980).…”
Section: -1960mentioning
confidence: 99%
See 2 more Smart Citations
“…Hampton & Scott (1980) reviewed the literature and suggested that the explanations previously suggested for the link between a reduction in blind seed disease and high fertility were not satisfactory, and that two other possibilities, originally suggested by Wilson et at. (1945), should be investigated: viz, that the use ofnitrogenous fertilisers altered the soil reaction and hence had some effect on apothecial development; that a vigorously growing crop may be physiologically less susceptible to attack than a poor thin one.…”
Section: Introductionmentioning
confidence: 99%